Land tenure reform and decentralization - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
There is renewed interest in land tenure reform policies in many countries as resources become more scarce and competition for land increases. Although the term “land reform” is still associated with redistribution of land, there are many types of land tenure reform or land policy.